Evaluation of the efficacy of cervical pessary combined with vaginal progesterone in women with a short cervix and additional risk factors for preterm delivery. (18th April 2021) - Daskalakis, George; Zacharakis, Dimitrios; Pergialiotis, Vasilios; Kalmantis, Konstantinos; Theodora, Mariana; Siristatidis, Charalambos; Antsaklis, Panagiotis; Antsaklis, Aris; Loutradis, Dimitrios
Abstract: Objective: The aim of this study was to examine the efficacy of a combined management with cervical pessary and vaginal progesterone of women with a singleton pregnancy and a short cervix in both low and high risk-cases based on their previous obstetrical history and maternal factors. Study design: This was a prospective cohort study of women with a singleton pregnancy and a sonographically detected mid-trimester cervical length ≤ 25 mm. The high-risk group consisted of women with a history of a previous spontaneous preterm birth (PB), or a second-trimester miscarriage, or a loop electrosurgical excision procedure of the cervix (LEEP) while the low-risk group of women without such a history. All women were managed with cervical pessary and daily vaginal administration of 200 mg of progesterone. The primary outcome measure was spontaneous delivery before 34 weeks (238 days) of gestation. Results: One hundred ninety-six cases with a CL ≤ 25 mm were detected during the study period. Fifty-two women declined to participate in the study. The remaining 144 women were divided into two groups based on the presence ( n = 44) or absence ( n = 100) of specific risk factors for PB. The rate of PTB < 34 weeks was similar in both low and high-risk pregnancies while a significantly higher rate of sPTB < 37 weeks was found in women with high-risk pregnancies ( p = .005). Conclusion: The combined treatment of cervical pessary and vaginal progesterone has a similar influence on preterm delivery rate < 34 weeks, in both low and high-risk women, with a mid-trimester short cervix.